The quantities in the Yupana from an Andean cultural perspective: An experience at classrooms of first and second grade of primary school (Edma 0-6: Educación Matemática en la Infancia, 2021)
In this study we present an analysis of the historical and cultural conception of quantity constructed by the South American high Andean societies. Our purpose is to make possible his pedagogic adaptation through an also resource culturally own how the Yupana is. In this sense, we laced the activities of the people in a sociocultural context Andean with the school activities. Specifically, the construction of significances of quantity and his basic operations in children that they initiate the school basic training. The used methodology is the case study. The collection of data consisted in the observations of activities at classroom.
Keywords: Mathematics Education; Intercultural education; Quantity; Yupana; Primary Education